Assessing the role of non-native species and artificial water bodies on the trophic and functional niche of Mediterranean freshwater fish communities - Toutain, Mathieu; Belouard, Nadège; Renault, David; Haubrock, Phillip J; Kurtul, Irmak; Aksu, Sadi; Emiroğlu, Özgür; Kouba, Antonín; Tarkan, Ali Serhan; Balzani, Paride (The Science of the total environment, 2024)
Habitat alterations and the introduction of non-native species have many ecological impacts, including the loss of biodiversity and a deterioration of ecosystem functioning. The effects of these combined stressors on the community trophic web and functional niche are, however, not completely clear. Here, we investigated how artificial ecosystems (i.e. reservoirs) and non-native species may influence the trophic and functional niche space of freshwater fish communities. To do so, we used carbon and nitrogen stable isotope and abundance data to compute a set of isotopic, trait, and functional metrics for 13 fish communities sampled from 12 distinct ecosystems in Türkiye. We show that in reservoirs, fish were more similar in their trophic niche compared to lakes, where the trophic niche was more variable, due to higher habitat complexity. However, there were no differences in the trait and functional metrics between the two ecosystem types, suggesting a higher prey diversity than assumed in reservoirs. We also found that the number of non-native species did not affect the trophic niche space, nor the trait or functional space occupied by the fish community. This indicates that non-native species tended to overlap their trophic niche with native species, while occupying empty functional niches in the recipient community functional space. Similarly, the proportion of non-native species did not affect any trophic, trait, or functional metric, suggesting that changes in community composition were not reflected in changes in the community niche space. Moreover, we found that trait richness, but not functional richness, was positively related to the isotopic niche width and diversity, indicating that a wider occupied trait niche space corresponded with a wider occupied trophic niche and lesser interspecific similarity. Our findings underscore the complexity of ecological relationships within freshwater ecosystems and highlight the need for comprehensive management strategies to mitigate the impacts of human activities and biological invasions.
Keywords: Functional niche; ryby; Food Chain; Ecosystem; Environmental Monitoring; Functional ecology; Lakes; zvířata; Isotopic niche; jezera; sladká voda; monitorování životního prostředí; Fishes; biodiverzita; Fresh Water; Fish assemblage; Stable isotope analysis; zavlečené druhy; Animals; Introduced Species; Functional traits; potravní řetězec; ekosystém; Biodiversity